Estimation of Serum Liver Enzymes Activities in Awassi Sheep: H.A.H. Al-Hadithy@1; N.M. Badawi1 and M.M. Mahmood2 - Al-Hadithy, H.A. H. (The Iraqi Journal of Veterinary Medicine, 2013)
The current study was conducted on 152 clinically normal Awassi sheep to evaluate serum activities of alanine aminotranferase (ALT), aspartate amino-transferase (AST), alkaline phosphatase (ALP) and gamma glutamyltransferase (GGT) in Baghdad governorate / Iraq. Sheep were divided into males; 62 ram lambs and rams, 90 females; ewe lambs, pregnant and lactating ewes both aged 7 to 48 months. The samples were collected from October 2011 until March 2012, and the sera were used for measurement of serum liver enzymes.The results revealed that the range and mean ± SEM of these enzymes were as follows : serum ALT 3.5 – 24 U/L and 9.66 ± 0.31 U/L, serum AST 25 – 220 U/L and 71.83 ± 3.09 U/L , serum ALP 59 – 300 U/L and 139.86 ± 3.56 U/L and serum GGT 2.3 – 38.2 U/L and 15.9 ± 0.78 U/L respectively. There were significant differences (P<0.05) between males and females in serum ALT and GGT activities. The effect of age on serum liver enzymes was studied in males. However, according to physiologic status a significant difference (P<0.05) noticed in serum enzymes values of all groups. In conclusion, present data recorded range references and mean ± SE for serum liver enzymes in normal Iraqi Awassi sheep with significant differences in activities of these enzymes between males and females a well as between subgroups in both sexes